Osobennosti podgotovki sportsmenov s poraženiem oporno-dvigatel'nogo apparata (PODA), zanimajušcichsja volejbolom sidja, v respublike Sacha (Jakutija) - Gavriliev, K. D.; Kolodeznikova, S. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Currently, more and more attention is paid to the people with disabilities in a state of health in order to achieve their maximum socialization and integration into society. The article discusses the selection of a sitting volleyball training technique for athletes with a musculoskeletal system lesion in the process of training camps. The analysis of the impact of training sessions on the physical condition of volleyball players with damage to the musculoskeletal system is presented.